Application of SERVQUAL Model to Gauge Relationship between Service Commitment, Trust, and Price Fairness to Customers Loyalty: Empirical Evidence of Telecommunication Users in Nepal (Quest Journal of Management and Social Sciences, 2024)
Background: The service sector, a significant contributor to global GDP, is increasingly focused on innovation, particularly in the telecom industry. Despite its importance, research on how service commitment, service trust, and price fairness affect customer loyalty within Nepal’s telecommunications sector remains limited.Objective: This study aims to investigate the impact of service commitment, service trust, and price fairness on customer loyalty in the mobile telecom sector in Kathmandu Valley. It seeks to apply the SERVQUAL model to assess how these factors influence customer retention and satisfaction.Method: An explanatory research design was employed using a quantitative approach. Data were collected through a structured questionnaire from 404 telecom users selected via purposive sampling. The analysis was conducted using structural equation modeling (SEM) with confirmatory factor analysis and path analysis, employing software tools such as KOBO Toolbox and AMOS to examine the relationships among variables.Result: The findings indicate that service commitment, service trust, and price fairness significantly impact customer loyalty. Service trust and price fairness were found to have a positive and significant effect on loyalty, with price fairness exhibiting a partial mediating role between service commitment and customer loyalty. The study also highlights that telecom firms’ ability to enhance customer satisfaction is closely linked to their service innovation and commitment.Conclusion: The research underscores the importance of service commitment, trust, and price fairness in fostering customer loyalty within Nepal’s telecom sector. Telecom service providers are encouraged to focus on these areas to improve service quality and customer retention. The study offers valuable insights for enhancing customer satisfaction and achieving long-term loyalty in the telecommunications industry.Paper Types: Research PaperKeywords: Telecommunication Service; Commitment; Service Trust; Price Fairness; Customer Loyalty; SERVQUAL model; Structure Equation Model.JEL Classification: D12, L86, L96, M31